Hemolytic disease of newborn caused by multiple Rh antibodies - Routray, Suman Sudha; Behera, Rachita; Sahoo, Jagdish Prasad; Acharya, Devi Prasad; Pati, Bibudhendu (International Journal of Contemporary Pediatrics, 2019)
Hemolytic disease of Fetus and Newborn (HDFN) usually results due to natural occurring antibodies or alloimmunization in mother but the presence of multiple red cell antibodies increases the risk of development of significant HDFN. Here author reported a case of hemolytic disease of fetus and newborn in a preterm baby caused by multiple maternal antibodies. Direct Antiglobulin Test (DAT) on neonate blood sample was positive (3+) with monospecific DAT showed IgG type which was confirmed by heat elution. Antibody identification of eluate was done using commercial 11-cell panel by gel method showing specificity to anti-D and anti-C antibody which was differentiated from anti-G by sequential adsorption and elution studies. Neonate was treated with double volume exchange transfusion (DVET) using leucoreduced, irradiated O Rh D and C negative PRBC suspended in AB plasma and discharged 6th day in a stable condition. So, all pregnant women should be at least advised for ICT irrespective of Rh D negative status. If ICT is positive, they should be referred to higher center for proper Immunohematological work up, so that proper blood unit for DVET could be identified.